Peran Guru IPS dalam Meningkatkan Minat Belajar Siswa di Masa Pandemi Covid-19 di SMP Negeri 1 Sindue Kabupaten Donggala - Dermawan, Ade; Jamaluddin (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2022)
This research was conducted at SMP Negeri 1 Sindue of Sindue Subdistrict, Donggala District. This research aims to know the role of social studies teachers and the factors that support and inhibit social studies teachers in increasing student interest in learning during the Covid-19 pandemic at SMPN 1 Sindue. The subjects of this research were 3 social studies teachers and 30 students. The data were collected through observation, interviews, questionnaires, and documentation. The results indicate the role of the teacher as a motivator in increasing interest in learning social studies of students at SMPN 1 Sindue, namely: teachers help students with learning difficulties, teachers give gifts to students, teachers use varied learning methods, teachers give praise to students, teachers give tests, teachers give a value in the form of numbers, and the teacher informs the learning outcomes. Social studies subject teachers in increasing student interest in learning have played a role for their students. It can be seen using a questionnaire, students' interest in learning is still quite good even in the Covid-19 pandemic. The supporting factors for the social studies teacher's role in increasing student interest in SMP Negeri 1 Sindue during the pandemic are: Student's sincerity in learning, students' health, support from the students' parents for student learning activities, and teacher competence. The inhibiting factors are student learning difficulties due to students' low level of understanding and factors of facilities and infrastructure from students for online learning, such as smart phone and network coverage.